Autentikasi Centella asiatica (L.) Urb. (Pegagan) dan Adulterannya Berdasarkan Karakter Makroskopis, Mikroskopis, dan Profil Kimia - Maruzy, Anshary; Budiarti, Mery; Subositi, Dyah (Jurnal Kefarmasian Indonesia, 2020)
Pegagan or Centella asiatica (L.) Urb. empirically used as medicinal plant and scientifically can be used as antihypertension based on the results of the Jamu Saintification. Raw materials from C. asiatica have the potential to occur adulteration or incorrect use of plants species. There are two species of plants that have the potential to become adulterants of C. asiatica, namely Hydrocotyle verticillata and Merremia emarginata. Thus, the purpose of this study is to authenticate from Pegagan by comparing the macroscopic, microscopic, and chemical profiles of C. asiatica, H. verticillata, and M. emarginata. The method of data collection is done by purposive sampling using form intruments to record macroscopic and microscopic characters, while the chemical profiles are tested using thin layer chromatography methods to determine the content of asiaticosides in both potential adulterants species. The research was conducted at three sampling points: Central Java (Tawangmangu), West Java (Bogor), and East Java (Malang), while for laboratory research activities carried out at B2P2TOOT, Tawangmangu. The results showed macroscopically unique and easy distinguishing characters between C. asiatica and potential adulterant species H. verticillata is a leaf shape, whereas C. asiatica with M. emarginata are leaf-type appearance characters. The character of the simplicia leaf shape between C. asiatica and H. verticillata can be a distinct differentiator characters. Anatomical characters and powder fragments that can be used as a differentiator characters between C. asiatica and H. verticillata are the presence of pith on the stalk and stolon, the type of stomata, and the presence of trichomes. Authentication of simplicia powder of H. verticillata as an adulterant potential of C. asiatica with TLC, can be easily known by the absence of asiaticosides in these simplicia so that H. verticillata cannot be a substitute species for C. asiatica